IMPROVING THE QUALITY OF EDUCATION IN THE CONDITIONS OF MARTIAL STATE BY USING VIRTUAL LABORATORY WORK (Innovative professional education, 2024)
Today, improving the quality of education in wartime and postwar times through the use of virtual laboratory work is an urgent task. As a result of the conducted research, virtual laboratory work has been developed, which is necessary in cases when it is economically impractical to conduct real laboratory work, for example, when studying the impact of certain emergency situations of the engine on its technical condition and it is difficult to conduct real laboratory work due to special requirements, in the conditions of war and post-war times.
Keywords: virtual laboratory work, virtual learning mode, knowledge control mode, virtual experiment